Brazil's agribusiness economic miracle: Exploring food supply chain transformations for promoting win-win investments - José Elenilson Cruz; Gabriel Medina; Jo\~ao Ricardo de Oliveira Júnior (Logistics, 2022)
Background: For many developing countries, agribusiness has become one of the main economic sectors, with the capacity to mobilize domestic and foreign investments. Despite the potential for development in countries like Brazil, the results of these investments in supply chains have not yet been systematically assessed. Methods: This study analyses foreign and domestic investments as an explanation for the recent growth of Brazilian agribusiness and evaluates the implications of different investment arrangements for the future development of the sector in the country. The research was based on a literature review of 12 agribusiness supply chains in Brazil. Results: Through a content analysis, the results reveal win-win situations with foreign and domestic investments supporting the streamlining of supply chains, mutually benefiting domestic and international groups and increasing the productivity of the entire sector. However, the results also reveal win-lose cases with chains and segments practically controlled by foreign multinationals in which local groups have practically no share. Finally, there are also cases of lose-win in which groups subsidized by the state are privileged in relation to others, compromising the sector's growth. Conclusions: The current liberal business environment results in the need for a new vision of development based on win-win opportunities for domestic and foreign investments created by dynamic sectors such as agribusiness.
Keywords: 650; alternative food supply chain models; conceptualizations of food supply chain transformations; foreign direct investment (FDI); ongoing evolutions and transformations; patents